2002
DOI: 10.1021/je0255067
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Silica Gel + Water Systems

Abstract: The adsorption characteristics of pure water vapor onto two different types of silica gel at temperatures from (298 to 338) K and at different equilibrium pressures between (500 and 7000) Pa were experimentally studied by a volumetric technique. The thermophysical properties such as the skeletal density, Brunauer−Emmett−Teller surface area, pore size, pore volume, and total porosity of silica gel were determined. The Tóth isotherm model is found to fit all of the experimental data within the experimental error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(71 citation statements)
references
References 7 publications
(21 reference statements)
3
63
0
1
Order By: Relevance
“…Figure 8 shows the cooling Coefficient Of Performance (COP) calculated for the composite sorbent S6 by a previously developed mathematical model (Cacciola and Restuccia 1995). The same figure reports the COP calculated for the silica gel "Fuji Davison RD"-water as working pair, which is used in commercialized adsorption chillers (Chua et al 2002). It was found that, depending on the operating conditions, the composite sorbent S6 allows to obtain acceptable COP values that are about 15-25% lower than those calculated for the silica gel.…”
Section: Performance Evaluationmentioning
confidence: 81%
“…Figure 8 shows the cooling Coefficient Of Performance (COP) calculated for the composite sorbent S6 by a previously developed mathematical model (Cacciola and Restuccia 1995). The same figure reports the COP calculated for the silica gel "Fuji Davison RD"-water as working pair, which is used in commercialized adsorption chillers (Chua et al 2002). It was found that, depending on the operating conditions, the composite sorbent S6 allows to obtain acceptable COP values that are about 15-25% lower than those calculated for the silica gel.…”
Section: Performance Evaluationmentioning
confidence: 81%
“…Indeed, the survey of water vapour adsorption equilibrium data of a number of microporous silica gels and zeolites, suggested for AC (Aristov et al, 2006a;Chua et al, 2002;Choi and Jeong, 2005;Dawoud and Miltkau, 2002;Baker and Kaftanoglu, 2007), (Figure 2(a)) shows rather small variation in uptake for the AC cycle considered. For desorption temperature T des = 85°C the uptake variation for most of the adsorbents is ∆w = 1-2%.…”
Section: Porous Adsorbents Of Water and Methanol Vapourmentioning
confidence: 96%
“…The adsorbent for water is silica gel (type A), while adsorbents for other refrigerants are activated carbons. The isotherm equations of these refrigerantadsorbent pairs were taken from literatures [6,2,3,1,5]. The calculation of the COP and SCE was based on an adsorption cooling cycle with refrigerant evaporation temperature of 10 • C, adsorption temperature of 30 C, condensation temperature of 30 • C and desorption temperature of 50 C to 100 C. It was assumed that the heat capacity ratio, M hex c hex /(M ac c ac ) equaled to 2, which is a reasonable value for a fin and tube type adsorption heat exchanger.…”
Section: Comparison Of the Theoretical Copmentioning
confidence: 99%
“…By a fitting of measured data with Dubinin-Astakhov (D-A) equation, we obtained adsorption isotherm equation for SAC-2 as in Eq. (6). (6) where, W 0 is 1.98 kg/kg, n is 1.5, and E is 90 kJ/kg.…”
Section: Analysis Of Theoretical Adsorption Cycle Performance With Sac-2mentioning
confidence: 99%